Knowledge and Attitudes of Patients with Advanced Heart Failure Toward Heart Transplantation - Türen, Selahattin; TÜREN, SEVDA (Van Tıp Dergisi, 2023)
Introduction: The increased prevalence of heart failure (HF) has also led to an increased prevalence of advanced HF. Heart transplantation (HTx) is still considered the "gold standard therapy" in the treatment of advanced HF. We sought to determine the attitudes and knowledge of patients with advanced HF toward HTx. Materials and Methods: This is a cross-sectional study conducted in an outpatient advanced HF and transplant clinic in a tertiary care center from February 2021 to January 2022 and 110 patients were included. Results: The mean age was 49.5±10.50 years and 82.7% of the patients were male. The majority of the patients (77.2%) stated that they thought HTx was religiously appropriate. However, only 50.6% of patients stated that if they were healthy, they would have donated their organs. 49.2%, received education about HTx. Only 27.3% of the patients found the education they received sufficient. The patients who received education about HTx had significantly better knowledge regarding the pre-transplant evaluation process and adverse conditions that may develop after HTx. There were no significant differences in terms of patients' knowledge and attitudes toward the HTx according to quality of life. Only the Minnesota Living with Heart Failure Questionnaire score of the patients who were afraid of surgery was found to be significantly higher. Conclusions: Patients did not have sufficient knowledge about HTx, but they had a positive attitude toward it. A multidisciplinary team should address the concerns of the patients, and assist the patients in adapting to the HTx process by providing the necessary education.
İleri Evre Kalp Yetersizliği Hastalarının Kalp Nakline Yönelik Bilgi ve Tutumları
Keywords: Advanced Heart Failure; Heart Transplantation; Knowledge; Attitude; Quality of Life